2012 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2012
DOI: 10.1109/robio.2012.6491159
|View full text |Cite
|
Sign up to set email alerts
|

Ethological evaluation of human-robot Interaction: Are children more efficient and motivated with computer, virtual agent or robots?

Abstract: Abstract-Nowadays, robots and virtual agents become companions for humans. They seem to have distinct roles in the Human-Agent Interaction. Thus, when developing a new application, it is judicious to wonder which the better is. In the Robadom project, a homecare robot has to assist elderly at home. The robot provides cognitive stimulation game. We developed StimCards, a cognitive card-based game. The principle question is: is the robot the best interlocutor in this context? This paper presents an evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…1 and considering similar research questions as those proposed here, in particular Wainer et al (2006Wainer et al ( , 2007 and Kiesler et al (2008). Some work has also grouped copresent and telepresent robot conditions into a single category for statistical analysis (e.g., Kiesler et al, 2008) or compared agents that have different morphologies (e.g., Heerink et al, 2009a;Jost et al, 2012a;Komatsu et al, 2011a), which presents a substantial confound for those reported results; instead, agents of similar morphology and appearance would better test hypotheses related to physicality and virtuality. At a minimum, these considerations can be acknowledged when generalizing from a given experiment to broader theoretical concepts.…”
Section: Implications For Methodological Designmentioning
confidence: 91%
“…1 and considering similar research questions as those proposed here, in particular Wainer et al (2006Wainer et al ( , 2007 and Kiesler et al (2008). Some work has also grouped copresent and telepresent robot conditions into a single category for statistical analysis (e.g., Kiesler et al, 2008) or compared agents that have different morphologies (e.g., Heerink et al, 2009a;Jost et al, 2012a;Komatsu et al, 2011a), which presents a substantial confound for those reported results; instead, agents of similar morphology and appearance would better test hypotheses related to physicality and virtuality. At a minimum, these considerations can be acknowledged when generalizing from a given experiment to broader theoretical concepts.…”
Section: Implications For Methodological Designmentioning
confidence: 91%
“…Bainbridge et al ( 2011) presented results for a book-moving task in which the artificial agents requested unusual behaviors such as throwing books into the trash; the results showed higher compliance rate when requests came from a physical robot than when they came from a virtual agent. In learning tasks, Jost et al (2012a) also showed children to be significantly more motivated by a physical robot when playing a cognitive-simulation game.…”
Section: Differences In Task Performancementioning
confidence: 95%
“…We concluded that AmbiProg could be an efficient "all audience" tool which could allow everyone to control easily a digital environment. Two other experiments investigated the use of different output devices as companion for the participants [6] [7]. The objective was to determine whether children and seniors had a favorite companion to interact with StimCards.…”
Section: A Previous Experimentsmentioning
confidence: 99%
“…Thus, it was important to check if the visual programming language (AmbiProg) was easily usable and understandable. Then, two experiments [6][7] compared children and seniors about their favorite companions. They interacted with a computer, a robot and a virtual character.…”
Section: Introductionmentioning
confidence: 99%